Pengaruh Penggunaan Media Proyeksi Terhadap Hasil Belajar Matematika - Dwi Dani Apriyani (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
Influence of media usage of projection to learning result of Math, knowing the influence of media usage of projection to student learning result of mathematics. Methods in this study with quasi-experimental methods. Samples were taken by simple random sampling from a population of 110 students by taking 60 respondents who were determined to be experimental class and control class. Data analysis using descriptive statistic method and test technique requirement of data analysis with normality test and homogeneity test. The result of the research shows that the experimental class that is using the projection media has good or higher learning result compared to control class that is using conventional media. So it can be said there is the influence of media usage of projection to result of learning mathematics in wake up flat side room.